THE SIGNIFICANCE OF DEVELOPING WELL-BEING SKILLS IN TEACHER TRAINING - Boda, Tímea (Acta Carolus Robertus, 2021)
The aim of the paper is to point at the significance of well-being skills in the personal and professional efficiency of students in teacher education. A paradigm shift has started in higher education: the guidelines of the World Economic Forum’s Education 4.0 and the establishment of the European Well-being University justify that well-being is a fundamental resource that determines the effectiveness of university students, helps their self-realization and their creative thinking and equips them with skills and attitude to give adequate reactions to societal and economic changes. This has a great significance in teacher training because the personal well-being of an educator has a multiplier effect; they are capable of influencing the mood, emotional fitness, mental and emotional well-being of the children they shape. For future generations, it is decisive what kind of attitude and points of view they experience in the period when their personality can be flexibly shaped. The present study also demonstrates that conscious development of these skills in teacher training is very timely; the results support that the overall well-being of students is inadequate.
Keywords: emotional well-being; teacher training; skills development; positive psychology; change of attitude